Thyristor Controlled Series Capasitor Berbasis Adaptive Fuzzy Logic Controller Sebagai Percepatan Peredaman Osilasi Daya Pada Sistem Tenaga - Dwi Agus Prabowo; Istiyo Winarno (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
The current population growth is very fast, so also the number of settlements more evenly, with this demand fulfillment demand for electricity is increasingly widespread and more, therebr making electric power generation service providers continue to strive to provide uniform and stable electrical energy. On the other hand there is an impact due to the many loads on the network electricity that can not be estimated its use, rise and fall of the load, therefore the power system stability must be maintained, this makes the stability of the power system the main concern in a operating. Without good dampening the disturbance will be isolated in the system and out of the stability area, so it can lead to worse effects such as total blackout. Thyristor Controlled Series Capacitor (TCSC) is a device that can be used to regulate power inmadance of power system. TCSC has three main components such as inductor, capacitor, and thyristor. The way TCSC works is by setting the angle of ignition, here the adaptive fuzzy controller is used as the best alpha-viewer the system needs. From the comparison simulation, the difference of fuzzy controller with adaptive fuzzy with fuzzy controller can reduce oscillation at 0.68 second average time and with fuzzy oscillation adaptive controller that can be muffled at 0.56 seconds, with this adaptive fuzzy controller capable damping oscillations 0.12 seconds faster in comparison with fuzzy controllers. So with this oscillation damping can reduce the impact of isolated disturbances in the system.